Legal Regulations for Advertising Vocational Education and Training Services: Case Study of Lithuania - Vidmantas Tutlys; Genute Gedviliene; Skaiste Vaiciukyniene (European Scientific Journal, ESJ, 2018)
The European Commission’s Europe 2020 strategy calls for the enhancement the attractiveness of vocational education and training. This article aims to disclose and critically discuss the requirements defined in legislation of Lithuania for advertising VET services with reference to the context of the improvement of the VET image in society. It seeks to determine the requirements stipulated in legislation of Lithuania for advertising VET services and to evaluate the information on admissions to institutions of vocational education and training on their web pages according to the criterion of truthfulness of advertising. The article may be useful for professionals who work or will work with marketing communication in the future. It can be used as a manual of how to inform customers about VET services properly. The methods applied in this research are content analysis of scientific literature and legal documents, linguistic, comparative, systematic and logical interpretation methods of law, and a qualitative content analysis used for the case study. The content of the training service and not the subjective image is the actual marketing object, because the content provides an advantage that ensures good market positions in increasingly competitive market of VET provision. The image of initial vocational education is determined not so much by the actions of society, but by the vocational training systems themselves, or more specifically by the targeted efforts of its participants to improve the quality of initial vocational education, responding to the public challenges and communicating this message to the interested audiences in the communication process.